Geophysical investigations of a potential landslide area in Mayoon, Hunza District, Gilgit-Baltistan, Pakistan (Rudarsko-geološko-naftni zbornik, 2021)
The Mayoon landslide in the Hunza District is a slowly developed, non-catastrophic landslide that has gained its importance in the last few years after its rapid activation and fast slip rate. The area is characterized by high earthquake hazards (zone 3 with a peak ground acceleration value of 2.4–3.2 m/s2) by the Building Code of Pakistan due to frequent earthquakes. The past high earthquake activity in the area has displaced the foliated rocks towards the south and is responsible for opening the bedrock joints. The head and body of the landslide are covered by unconsolidated material and have fractures of varying lengths and widths. The non-invasive geophysical techniques, including Ground Penetrating Radar (GPR) and Electrical Resistivity Soundings (ERS), are deployed to evaluate the Mayoon landslide subsurface. The subsurface is interpreted into a two-layer model. Bright reflectors and highly variable resistivity characterize the top layer (Layer-1). This layer is associated with a loose, highly heterogeneous, fragmented material deposited under glacial settings over the existing bedrock. Hyperbolic reflections and intermediate resistivity characterize the bottom layer (Layer- 2). This layer is associated with foliated metamorphic bedrock. The hyperbolic reflections show faults/fractures within the bedrock. The extension of these fractures/faults with depth is uncertain due to decay in the GPR signal with depth. The intermediate resistivity shows the bedrock is weathered and foliated. Reflections within Layer-1 have disrupted directly above the fractures/faults suggesting a possible movement. A bright reflection between the two layers highlights the presence of the debonded surface. Loose material within Layer-1 coupled with debonding possesses a significant hazard to generate a landslide under unfavourable conditions, such as an intense rainstorm or earthquake activity.